RESEARCH OF AN AUTONOMOUS ENERGY SUPPLY SYSTEM BASED ON A COGENERATION BIOENERGY DEVICE - Rustamov, Sukhrob; Davlonov, Khayrulla (Innovatsion texnologiyalar, 2023)
In this research work, initial experiments and analyzes of the device for obtaining alternative fuels through the thermal processing of biomass waste, providing autonomous consumers with heat and electricity are presented. During the research, the structural structure of alternative fuels obtained by thermal processing of various biomass wastes at a temperature of 400-500 0C in a pyrolysis device was studied. The thermal technical characteristics of the alternative fuel production process and the factors influencing them were carried out on the basis of scientific and theoretical analyses. Also, thermal and energy schemes of the experimental device were developed and parameters were based.